Environmental plasticity of Pinot noir grapevine leaves: A trans‐European study of morphological and biochemical changes along a 1, 500‐km latitudinal climatic gradient. (27th September 2017) - Castagna, Antonella; Csepregi, Kristóf; Neugart, Susanne; Zipoli, Gaetano; Večeřová, Kristýna; Jakab, Gábor; Jug, Tjaša; Llorens, Laura; Martínez‐Abaigar, Javier; Martínez‐Lüscher, Johann; Núñez‐Olivera, Encarnación; Ranieri, Annamaria; et al.
Abstract: A 2‐year study explored metabolic and phenotypic plasticity of sun‐acclimated Vitis vinifera cv. Pinot noir leaves collected from 12 locations across a 36.69–49.98°N latitudinal gradient. Leaf morphological and biochemical parameters were analysed in the context of meteorological parameters and the latitudinal gradient. We found that leaf fresh weight and area were negatively correlated with both global and ultraviolet (UV) radiation, cumulated global radiation being a stronger correlator. Cumulative UV radiation (sumUVR) was the strongest correlator with most leaf metabolites and pigments. Leaf UV‐absorbing pigments, total antioxidant capacities, and phenolic compounds increased with increasing sumUVR, whereas total carotenoids and xanthophylls decreased. Despite of this reallocation of metabolic resources from carotenoids to phenolics, an increase in xanthophyll‐cycle pigments (the sum of the amounts of three xanthophylls: violaxanthin, antheraxanthin, and zeaxanthin) with increasing sumUVR indicates active, dynamic protection for the photosynthetic apparatus. In addition, increased amounts of flavonoids (quercetin glycosides) and constitutive β‐carotene and α‐tocopherol pools provide antioxidant protection against reactive oxygen species. However, rather than a continuum of plant acclimation responses, principal component analysis indicates clusters of metabolic states across the explored 1, 500‐km‐long latitudinal gradient. This study emphasizes the physiological component of plant responses to latitudinal gradients and reveals the physiological plasticity that may act to complement genetic adaptations. Abstract : In this paper, morphological and biochemical parameters (flavonoid and carotenoid composition, non‐enzymatic leaf total antioxidant capacity and ultraviolet (UV)‐absorbing pigment content) of Pinot noir grapevine leaves were measured at different vineyards across a 1, 500‐km latitude gradient in Europe. We identified cumulative UV radiation as the strongest correlator with most leaf metabolites and pigments and also found that leaf fresh weight and area were negatively correlated with both global and UV radiation. The acquired data set also allowed the analysis of complex interactions between various classes of metabolites in responding to environmental conditions. The study emphasizes the physiological component of plant responses to latitudinal gradients and reveals the physiological plasticity that may act to complement genetic adaptations.